2018
DOI: 10.1080/15592294.2018.1518100
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of imprintedIGF2regions is associated with total, visceral, and hepatic adiposity in postmenopausal women

Abstract: Excess body fat, especially intra-abdominal fat, is a leading risk factor for metabolic diseases. Differentially methylated regions (DMRs) of two imprinted genes, insulin-like growth factor 2 (IGF2) and H19, have been associated with obesity due to their important roles in regulating body composition, but have not been examined in relation to intra-abdominal fat depots. Total body fat from whole-body dual energy X-ray absorptiometry and visceral and liver fat contents from abdominal magnetic resonance imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Research has shown that excessive levels of body fat, particularly intraabdominal fat, is a leading risk factor for the development of metabolic diseases. Furthermore, methylation levels of DMR regions in the IGF2 gene in leukocytes have been associated with total body fat content and the distribution of fat in the viscera and liver in manner that was independent of total adiposity [45]. These data are indicative of a potential association between IGF2 and PCOS.…”
Section: Discussionmentioning
confidence: 79%
“…Research has shown that excessive levels of body fat, particularly intraabdominal fat, is a leading risk factor for the development of metabolic diseases. Furthermore, methylation levels of DMR regions in the IGF2 gene in leukocytes have been associated with total body fat content and the distribution of fat in the viscera and liver in manner that was independent of total adiposity [45]. These data are indicative of a potential association between IGF2 and PCOS.…”
Section: Discussionmentioning
confidence: 79%
“…33,57 There is evidence that epigenetic alteration at these DMRs from the early life environment is persistent-even into late adulthood 58 -and contributes to adverse health outcomes including low birth weight, adolescent adiposity, and adiposity in post-menopausal women. [34][35][36]57 While epigenetic regulation of IGF2 and H19 seem to play a role in obesity and metabolic conditions later in life, how or whether this starts to develop in childhood or adolescence is unknown. Examined separately, lower levels of dicarboxylic fatty acids have been previously associated with obesity in children 5,9 and H19 methylation is positively associated with adiposity including among 17-year old children.…”
Section: Discussionmentioning
confidence: 99%
“…These genes and the LINE-1 biomarker were selected due to evidence for environmental-lability by various exposures in early development 15 , 31 - 33 and for evidence of associations with adiposity-related outcomes in childhood or beyond. 34 - 36 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants for this study were recruited from the Multiethnic Cohort Study (MEC; 1993-current) [4]. As detailed previously [20,21], in 2009-2019, 60 overall healthy, postmenopausal women aged 60-65 were recruited among the MEC participants in Oahu, Hawaii, including self-identified 30 European Americans (EUA) and 30 Japanese Americans (JPA) selected after stratification on age and BMI. This ancillary study within the MEC was a pilot study to explore imaging-based body composition of JPA, who were observed to have higher risks for obesityrelated diseases and cancers in the MEC [5,7,8] despite their lower mean BMI compared to EUA among generally healthy individuals.…”
Section: Study Participantsmentioning
confidence: 99%